Identification and resolving of trace and co-eluted components of Lamium amplexicaule essential oil using two chemometric methods-assisted GC-MS - Fateme Tajabadi; Majid Ghorbani Nohooji; Reza Hajiaghaee (Shiraz University of Medical Sciences, 2024)
Gas chromatography-mass spectrometry (GC/MS) due to high sensitivity and qualifying the volatile compounds is one of the most practical methods for the analysis of essential oils. Accurate identification of trace components and complete separation of overlapped and embedded peaks are difficult to achieve even if precise conditions are imposed on the chromatographic separation process. In this study, the essential oil of Lamium amplexicaule L. (L. amplexicaule) after extraction by the Clevenger apparatus, was analyzed by GC/MS. This study focuses on the characterization of the trace and co-eluted components of essential oils in the mentioned species using chemometric methods. Advanced multivariate curve resolution (MCR) methods were used to overcome the problem of background, baseline offset and overlapping peaks and recognition of the noises from the trace components in GC/MS. The analysis of GC/MS data without chemometric methods revealed that eighteen components exist in the L. amplexicaule essential oil. It is noteworthy that, by a combination of MCR with GC/MS method, this number was extended to more than twenty-five. Using chemometric tools and methods, components with a percent higher than 0.01%, were identified from noises and other overlapped peaks were resolved for 85.56% of the total relative content of the L. amplexicaule essential oil. The most important volatile constituents were identified as hexahydrofarnesyl acetone, spathulenol, caryophyllene oxide, hexadecanoic acid and trans-phytol respectively.